Delayed neurologic sequelae of carbon monoxide intoxication - Sönmez, Bedriye Müge (Turk J Emerg Med, 2018)
Altered consciousness and accompanying neurological symptoms are both complex and challenging cases for emergency physicians. These are not specific and may be a sign of a variety of medical conditions including stroke and delayed neurological sequelae (DNS) is a recurrent transient neuropsychiatric consequence of CO intoxication. DNS produces a spectrum of varying symptoms and the diagnosis is primarily made on the basis of clinical features and radiological findings from CT and conventional MRI. In clinical practice, serious CO intoxication is treated only with oxygen therapy although no effective treatment exists. Emergency physicians play a major role in managing patients presenting with CO intoxication and preventing DNS.